Co-Circulation of 2 Oropouche Virus Lineages, Amazon Basin, Colombia, 2024 - Usuga, Jaime; Limonta, Daniel; Perez-Restrepo, Laura S.; Ciuoderis, Karl A.; Moreno, Isabel; Arevalo, Angela; Vargas, Vanessa; Berg, Michael G.; Cloherty, Gavin A.; Hernandez-Ortiz, Juan P.; Osorio, Jorge E. (Emerging infectious diseases, 2024)
In early 2024, explosive outbreaks of Oropouche virus (OROV) linked to a novel lineage were documented in the Amazon Region of Brazil. We report the introduction of this lineage into Colombia and its co-circulation with another OROV lineage. Continued surveillance is needed to prevent further spread of OROV in the Americas.